S100 Calgranulin Proteins S100A8, S100A9 and S100A12 are Expressed in the Inflamed Gastric Mucosa of Helicobacter Pylori-Infected Children - Steven T Leach; Hazel M Mitchell; Carolyn L Geczy; Philip M Sherman; Andrew S Day (Canadian Journal of Gastroenterology, 2008)
The expression of the inflammatory S100 calgranulin proteins (S100A8, S100A9 and S100A12) in normal and Helicobacter pylori-infected gastric mucosa of children were examined. S100A8, S100A9 and S100A12, which were virtually absent in normal gastric mucosa, were highly expressed in H pylori-infected mucosa. This expression correlated with the severity of gastritis (r=0.9422, P<0.05). S100 calgranulins may be involved in bacterial-induced gastritis and may limit bacterial growth.